(untitled) (Dhaka University Journal of Biological Sciences, 2014)
Conventional microscopy, ELISA and Real Time PCR showed Giardia lamblia in a total of 4470 asymptomatic and 423 symptomatic faecal samples from urban slum children of 13 ? 60 months age old. ELISA showed more sensitivity (88.88%) and specificity (90.91%) than microscopy (6.5% sensitive and 100% specific). The prevalence of G. lamblia infection among asymptomatic children was 37.93% by microscopy and 76.11% by ELISA. The prevalence was 7.03, 38.91 and 66.49 by microscopy, ELISA and Real Time PCR in symptomatic children, respectively. The highest prevalence (80.95%) of infection was found in symptomatic children between 49 and 60 months old. Peak prevalence among asymptomatic children was found in March, 2012 (39.39%) and among symptomatic children in September, 2012 (88.88%). Giardia lamblia infection was higher (71.03%) in male than in female children (60.26%). DOI: http://dx.doi.org/10.3329/dujbs.v23i2.20100 Dhaka Univ. J. Biol. Sci. 23(2): 197-204, 2014